Literature, education and Republic. André Maurois and the instinct of bourgeois happiness (First part) - de la Arada, Raquel; Garcia Farrero, Jordi; Vilanou Torrano, Conrad (Historia y Memoria de la Educación, 2016)
This article describes the relationship between literature and the educational ideals of André Maurois (1885-1967). After a review of his formative years in the shadow of the philosopher Alain, who was his teacher at Rouen Lyceum, the paper goes on to highlight the presence of military elements in his educational universe The extent of this influence can be seen in the fact that, after the Dreyfus affair, the educational work undertaken during the Third French Republic (1870-1940) is best understood in the light of the combination between intelligence and weapons, that is, between the lyceum and the garrison. Maurois, who traveled throughout the United States, was concerned about the atmosphere of crisis in the decade of the twenties and thirties, and took inspiration from Marshal Hubert Lyautey in order to comprehend the characteristics of the art of leadership. This skill, together with the art of thinking, the art of loving, the art of working, and the art of growing old, give shape to the various aspects of Maurois’ The Art of Living (1939), which fits nicely in the best of French pedagogical traditions (Montaigne, Rousseau, Alain) and highlights the importance of the task of living. Ultimately, and from a bourgeois stance embracing order, Maurois intended for the human being to lead a happy life, in line with the Republican values inherited from the 1789 Revolution. In short, he was an intellectual who combined tradition and modernity in a changing world that, after World War I (1914-1918), left behind the false securities of the Belle Époque. An author who never forgot the perspective of human happiness beyond any metaphysical consideration, Maurois’ work had a great impact in Spain, before and after the Civil War. This paper expounds on the influence he exerted and the way he contributed decisively to changing the public sense of morality in our country.